Factors explaining the composition and diversity of vascular plant understories along a transcontinental gradient in the Canadian boreal forest. (1st August 2021) - Crispo, Maude; Jean, Mélanie; Fenton, Nicole J.; Leduc, Alain; Bergeron, Yves
Abstract: Aim: Impacts of longitudinal gradients on species distributions have received less attention than latitudinal gradients. In Canada, precipitation varies longitudinally, with direct effects on plant growth and fire regimes. Despite the geographical extent of Canadian boreal forests, vascular plant diversity is relatively limited, with just under 300 species. Understorey communities comprise most of this diversity and play key roles in forests, affecting succession, nutrient cycling and wildlife habitat. Our objective was to evaluate the relative impacts of local and regional environmental conditions on vascular plant community composition and diversity in the boreal forest. Location: Sampling took place in 33 trembling aspen ( Populus tremuloides ) stands along a transcontinental gradient in precipitation and fire regimes in boreal Canada. Methods: We measured community composition and vegetation diversity indices of the vascular understorey in 400‐m 2 plots and measured environmental variables at the local (drainage, nutrient and light availability, site heterogeneity) and regional (annual temperature and precipitation, fire weather index, landscape heterogeneity) scales. Multivariate analyses and hierarchical model selection were used to analyze patterns. Results: Species composition varied longitudinally, with western and eastern species pools. Western indicator species tended to be fire‐adapted pioneer species, while indicator species at eastern sites were fire avoiders and late‐successional species. Species richness and intra‐site beta diversity seemed primarily driven by local variables and did not vary across the country. Species evenness, however, was slightly higher in the western region and decreased under higher precipitation, colder temperatures, and higher landscape‐level heterogeneity. Conclusion: Our results suggested that even for similar canopy composition environmental variables play a key role in the establishment of plant communities and structure local plant assemblages by selecting or eliminating species from the regional pool, which was also controlled by fire regimes. Abstract : A transcontinental study through the boreal forest to evaluate the relative impacts of local and regional environmental conditions on vascular plant community composition and diversity. Our results suggested that even for similar canopy composition, environmental variables play a key role in the establishment of plant communities and structure local plant assemblages by selecting or eliminating species from the regional pool.